2020
DOI: 10.1038/s42003-020-0897-1
|View full text |Cite
|
Sign up to set email alerts
|

High temperatures alter cross-over distribution and induce male meiotic restitution in Arabidopsis thaliana

Abstract: Plant fertility is highly sensitive to elevated temperature. Here, we report that hot spells induce the formation of dyads and triads by disrupting the biogenesis or stability of the radial microtubule arrays (RMAs) at telophase II. Heat-induced meiotic restitution in Arabidopsis is predominantly SDR-type (Second Division Restitution) indicating specific interference with RMAs formed between separated sister chromatids. In addition, elevated temperatures caused distinct deviations in cross-over formation in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 48 publications
13
74
0
Order By: Relevance
“…To investigate the effect of zyp1 on the Class I interference-sensitive CO pathway, HEI10 foci numbers were compared between the mutant and wild type ( 56 ). HEI10 is the A. thaliana ortholog of S. cerevisiae Zip3 and promotes formation of Class I COs ( 57 ). In the wild type, as previously reported, a large number of foci were observed at late zygotene/early pachytene ( = 44.7, SD = 18.7, n = 14) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effect of zyp1 on the Class I interference-sensitive CO pathway, HEI10 foci numbers were compared between the mutant and wild type ( 56 ). HEI10 is the A. thaliana ortholog of S. cerevisiae Zip3 and promotes formation of Class I COs ( 57 ). In the wild type, as previously reported, a large number of foci were observed at late zygotene/early pachytene ( = 44.7, SD = 18.7, n = 14) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in C. elegans suggest that the SC TF proteins limit COs and attenuate CO interference ( 40 ). However, studies in S. macrospora indicate that interference acts on a large number of recombination initiation events (∼80) giving rise to a smaller number (∼45 to 50) of patterned, evenly spaced, synapsis initiation sites and CO designations, thereby arguing that CO patterning is established prior to SC formation ( 35 , 57 ). Studies in S. cerevisiae also support a model of early CO designation ( 6 , 32 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Arabidopsis have revealed that at 32°C, ASY1 foci appear normal but linear configuration of ZYP1 on pachytene chromosomes is interrupted (De Storme and Geelen, 2020). In barley, a moderate high temperature causes a slight but significant decrease of CO formation by affecting ZYP1-dependent SC assembly (Higgins et al, 2012).…”
Section: Chromosome Axis and Sc Assembly Are Prominent Targets Of Higmentioning
confidence: 98%
“…These results are consistent with the hypothesis that the regulation of ASY1 gene expression in uences meiotic recombination levels. However, recent studies in Arabidopsis reported no change in ASY1 immunostaining in wild type meiocytes after 30-32 °C heat shock for 24 hours [4], but partially compromised localization under 36-38 °C extreme heat stress conditions [31]. It is important to note that the regulatory responses to moderate environmental stresses may not be re ected in more extreme conditions which can instead result in meiotic failure.…”
Section: Discussionmentioning
confidence: 96%
“…In the absence of a CO, chromosomes segregate randomly, resulting in chromosome number imbalances, or aneuploidy, in the gametes which, in turn, can result in developmental defects or lethality in progeny. Regulation of the frequency and distribution of COs in the genome has been studied extensively [1] and more recently, advances have been made in our understanding of how environmental conditions and stressors in uence those regulatory mechanisms [2][3][4].…”
Section: Introductionmentioning
confidence: 99%